Various Scales of Aging Heterogeneities upon PEMFC Operation – A Link between Local MEA Materials Degradation and the Cell Performance. (14th September 2015) - Dubau, Laetitia; Durst, Julien; Castanheira, Luis; Maillard, Frederic; Lamibrac, Adrien; Dillet, Jérôme; Maranzana, Gaël; Lottin, Olivier; El Kaddouri, Assma; De Moor, Gilles; Bas, Corine; Flandin, Lionel; et al.
Abstract : PEMFC performances decay upon operation, following the degradation of their core materials. These degradations are heterogeneous within a PEMFC, whatever its operating conditions and its constitutive materials. Three distinct levels of degradation heterogeneities are observed in PEMFC cathodes. (i) The degradations are neither homogeneous along the gas channels of the bipolar plates (BP, from the inlet to the outlet), nor along the active layer thickness (from the membrane to the diffusion layer). (ii) The BP geometry also matters: repeated start/stop (fuel-starvation) events promote harsher degradation for the cathode regions facing the anode regions located under the BP land. (iii) Finally, the cells operate and age differently at the stack level. These degradations are strongly linked to the materials composing the MEA and the operating conditions, but also depend on the bipolar plates and stack design, which renders difficult any generalization of the conclusions obtained for a particular PEMFC test.